THE USE OF CLOZE PROCEDURE TO TEST THE STUDENTS READING COMPREHENSION - Susanti, Ike; Buan, Stevanus; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The use of cloze procedure to test the students reading comprehension. The purpose of this research is to know the effectiveness of the use of cloze procedure to test reading comprehension of the eleventh grade students of SMUN 1 Sungai Ambawang in academic year 2012/2013. The method of this research was a Pre-experimental Study and the technique of data collecting was matching test. The research findings showed the total score of pretest is 2735 with the mean score 68.375 and categorized Average. Furthermore, the result of posttest is 3155 with the mean score 78.875 and categorized Good. The result of computation on the t-test with 7.56 is higher than the t-table for the degree of freedom N-1 (40-1) = 39 is 2.042. Moreover, the computation on Effect Size of the treatment is 1.13. It is categorized Highly Effective because the result of 1.13 is higher than 0.8 that is the high level of effectiveness on Effect Size criteria proposed by Burn (ES > 0.8 = 1.13 >0.8). From the computation, it can be concluded that the teaching reading comprehension by using Cloze Procedure is highly effective. Keywords: cloze procedure, reading comprehension, effectiveness. Abstrak: Penggunaan prosedur cloze untuk mengajar siswa pemahaman membaca. Tujuan dari penelitian ini adalah untuk mengetahui keefektifan penggunaan presedur cloze untuk mengajar pemahaman membaca bagi siswa kelas sepuluh SMUN 1 Sungai Ambawang tahun ajaran 2012/2013. Metode yang digunakan dalam penelitian ini adalah Pre-eksperimental dan teknik pengumpulan data adalah uji pencocokan. Hasil penelitian menunjukkan bawha nilai total pretest adalah 2735 dengan nilai rata-rata 68.375 dan dikategorikan sebagai Sedang. Lebih jauh, hasil posttest adalah 3155 dengan nilai rata-rata 78.875 dan dikategorikan baik. Hasil perhitungan t-test dengan 7.56 lebih tinggi daripada t-table untuk tingkat kebebasan N-1 (40-1) = 39 adalah 2.042. Kemudian, perhitungan Effect Size treatment-nya adalah 1.13. Ini dikategorikan Sangat Efektif karena hasil 1.13 lebih tinggi daripada 0.8 merupakan keefektifan tingkat tinggi dari criteria Effect Size yang diberikan oleh Burn (ES > 0.8 = 1.13 >0.8). Dari perhitungan tersebut, dapat disimpulkan bahwa mengajar pemahaman membaca dengan menggunakan Prosedur Cloze adalah Sangat Efektif. Kata Kunci: prosedur cloze, pemahaman membaca, keefektifan.